Overview of Pilonidal Cyst Treatment Methods - Review Paper - Łukaszewska, Ewa; Sajkiewicz, Ilona; Miga-Orczykowska, Nadia; Jasiuk, Ilona; Lemieszek, Paulina; Wójtowicz, Justyna; Rudnicka, Katarzyna; Pustelniak, Martyna; Krukar, Katarzyna; Chrościński, Kamil (Journal of Education, Health and Sport, 2024)
Introduction and purpose A pilonidal cyst also known as a pilondial sinus, is an inflammatory condition that occurs in the intergluteal region, which can lead to serious infections. It most commonly affects young men, with risk factors including the presence of hair in this area, excessive sweating, obesity, and poor hygiene. Symptoms include a lump, pain, and purulent discharge from openings in the skin. Diagnosis involves taking a medical history, a physical examination, and often an ultrasound. The aim of this paper is to present and compare the available methods for treating pilonidal cysts. Materials and methods Literature available in PubMed databases were reviewed using the following keywords: ‘’Pilonidal cyst’’, ‘’Hair cyst’’, ‘’Abscess’’, ‘’Treatment of pilonidal cyst’’,’’ Bascom II method’’,’’ Limberg flap’’,’’ Suchorski technique’’, ‘’V-Y or Z skin flap reconstruction’’,’’ the Karadakis’’ Results The available treatment methods can be divided into conservative and invasive approaches. Conservative methods include hair removal and improved hygiene. Among the surgical methods, there are traditional excision techniques and modern methods such as excision using the Bascom II method, Limberg flap, Suchorski technique, or V-Y or Z skin flap reconstruction. The Karadakis method, which involves shifting a skin flap, is particularly effective for obese patients. Conclusion Treatment of pilonidal cysts depends on the stage and symptoms. Abscesses require urgent surgical intervention, while asymptomatic cysts can be treated conservatively or surgically.